Career Exploration System (C-EXSYS) in Era Society 5.0 Based on Expert System - Resmi Darni; Lativa Mursyida (Universitas Negeri Padang, 2021)
There are many strategies that have been launched by the government in increasing graduate marketing and reducing unemployment, but this program is only able to absorb 12% of graduates, this is still considered not optimal. In addition, each program is still separate or not integrated with one another, so that the data and information obtained are invalid, practical and effective. Based on the description above, graduate marketing problems can be classified as follows: 1) Job matching applications managed by vocational high schools are not optimal, 2) Existing applications have not been integrated with vocational high school programs that support graduate marketing, 3) Applications that support distribution programs Existing graduates have not been able to map and provide career recommendations and connect graduates with work partners. This article aims to explain the process of designing an integrated career expert system capable of recommending careers and jobs based on personality. The method used in this research is the 4D method, namely Define, Design, Development and Disseminate. The results of this study are an expert system application that is able to provide job recommendations based on six personality types focused on vocational. The results of the constructs validation test obtained a fit model where, the value of p = 0.26972 and RMSEA = 0.029, the expert validity test of the design aspects was 0.88 (Valid), Operation 0.88 (Valid), and Benefits 0.90 (Very Valid), practicality test results 0.83 (Practical).